Computed Tomography-Guided Percutaneous Lung Biopsy Complicated by Symptomatic Systemic Air Embolism: Case Report and Review of the Literature - Ledas, Giedrius; Jocius, Donatas; Jarašūnas, Juozas; Jagelavičius, Žymantas (Lietuvos chirurgija, 2021)
Computed tomography-guided percutaneous core needle biopsy of the lung is an undoubtedly useful and well-established interventional radiological procedure for the diagnosis of indeterminate pulmonary lesions. Complications of percutaneous core needle biopsy, such as pneumothorax and hemoptysis are considered mild and self-resolving, however systemic air embolism is considered a potentially fatal complication. Systemic air embolism occurs when the air enters a pulmonary vein secondary to a percutaneous CT-guided lung biopsy and is expelled into systemic circulation. Systemic air embolism is extremely rare: incidence of clinically apparent SAE is estimated at 0.061–0.17%, while clinically silent systemic air embolism may be as high as 3.8–4.8%. This study reports a case of air embolism in the cerebral arteries that resulted from a complex CT-guided percutaneous core needle biopsy of the lung. The present case highlights the main mechanisms of this pathology, risk factors, importance of complete thoracic CT after procedure, as well as management of rare complications.
Keywords: percutaneous core needle biopsy; lung biopsy; systemic air embolism